Characterization of pullulanase type II from Bacillus cereus H1.5 - Hii, Siew Ling; Ling, Tau Chuan; Mohamad, Rosfarizan; Ariff, Arbakariya (Science Publications, 2009)
Problem statement: Pullulanase is one of the important enzymes in starch industry. Search for the pullulanase with distinct features, possibly from easily grown bacterium, is of interest for industrial applications Approach: The extracellular pullulanase produced by Bacillus cereus HI.5 was purified by chromatographic method of DEAE-Sepharos e, followed by Superdex gel filtration. The enzyme was characterized in terms of the optimal pH and temperature for activity as well as substrate specificity. Results: The enzyme showed optimal activity at 55°C and pH 6.0. The thermostability and the thermoactivity of the enzyme were increased considerably in the presence of Ca2+. In the present of 2 mM Ca2+, the enzyme had half-life duration of more than 2 h at 50°C. Almost all metal ions had a strong inhibitory effect, except Ca2+ and Mn2+. The Ca2+ had a very strong stimulating effect on the enzyme, increasing its activity by 170%. The enzyme was activated by 2-mercaptoethanol and dithiothreitol, where as N-bromosuccinimide and Schardinger dextrins were inhibitors, suggesting that tryptophan and thiol residues may be important for the activity. The apparent Km and Vmax value for pullulan was 1.1 mg mL−1 and 0.275 μmol min−1, respectively. A relative substrate specificity for hydrolysis of pullulan, amylopectin and soluble starch by this pullulanase was 100%, 28.5% and 20.4%, respectively. Conclusion: The enzyme was able to attack specifically the α-1,6 linkages in pullulan to generate maltotriose as the major end product, as well as the α-1,4 linkages in amylopectin and soluble starch leading to the formation of a mixture of maltose and glucose and therefore be classified as a type II pullulanase or an amylopullulanase.